Penghayatan OMK terhadap Sikap Liturgi dalam Perayaan Ekaristi di Stasi Santo Yosep Pekerja Tewaan - Jearne Felix Imbang; Johanes Danny Surentu (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2025)
This study discusses the appreciation of the liturgical attitude in the celebration of the Eucharist. The method used is a qualitative research method. The results obtained in this study are an appreciation of the liturgical attitude for young Catholics and efforts that can be made to live up to the liturgical attitude in the Eucharist such as: additional basic material in religious lessons at school, parental supervision of children during the celebration Eucharist, catechesis and recollection of liturgical attitudes to increase understanding and appreciation of OMK.